PENDAMPINGAN UMKM DAN SOSIALISASI LAPORAN KEUANGAN TERHADAP KINERJA KEUANGAN UMKM - Devita, Hety (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
This study aims to analyze the effect of MSME assistance and dissemination of financial statements on MSME financial performance. The research method used was a survey using a structured questionnaire given to 100 respondents of MSME owners in the Balikpapan area. The results showed that MSME assistance and dissemination of financial statements have a significant influence on MSME financial performance. MSME assistance contributes positively to improving financial performance, while dissemination of financial statements plays an important role in increasing MSME financial transparency and accountability. The results of this study provide important implications for MSME owners to pay attention to the importance of mentoring and socializing financial statements in developing their business  MSME assistance, socialization of financial statements, MSME financial performance